(untitled) (Architecture Image Studies, 2026)
Sarcopenia is characterized by progressive loss of skeletal muscle mass and strength associated with aging, leading to decreased physical function and reduced quality of life. This systematic review aimed to comprehensively evaluate the effects of various exercise interventions on muscle mass, strength, and physical function in patients diagnosed with sarcopenia according to the Asian Working Group for Sarcopenia(AWGS) criteria. A systematic literature search of PubMed, Embase, and Cochrane identified 54,604 studies, of which seven randomized controlled trials(RCTs) were analyzed using the ACSM FITT-VP principle. The review found that low-to-moderate intensity aerobic and resistance exercises performed 3–5 times per week for 60 min resulted in significant improvements in muscle mass, strength, and physical function. Notably, combined exercise interventions that integrated aerobic and resistance training yielded the greatest benefits. However, the limited number of included studies and heterogeneity in the intervention protocols suggest the need for larger, more objective, and reliable future research.